MILITARY-CIVIL HEGEMONY ISSUES AND THEEFFORTS OF THE MINISTRY OF DEFENSE'S STATEDEFENSE DIRECTORATE IN THE STATE DEFENSEAWARENESS BUILDING PROGRAM IN LAMPUNG : AANTHROPOLOGICAL STUDY OF DEFENSE - Bartoven Vivit Nurdin; Arsella Mutiara Sindi (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This study explores the efforts of the Directorate of State Defense, Ministry of Defense, to foster State Defense awareness in the community through the State Defense Awareness Development Program (PKBN). Initially, this program was designed by the Indonesian Ministry of Defense as an effort to instill the values of nationalism and love of the homeland in the face of both military and non-military threats, especially among youth, community organizations, and civil society. However, these efforts still encounter obstacles in society, one of which is the perception and issue of military vs civilian hegemony. Using the anthropology of defense approach and Antonio Gramsci's theory of hegemony. According to Gramsci, lasting power is not only based on coercion, but also on agreements built through education, culture, and symbols in everyday life—and this is the state's primary role in the PKBN program. Bandar Lampung City, as a social space with a diverse population in terms of religion, ethnicity, and profession, is a strategic arena for the implementation of PKBN. This research uses qualitative methods, including in-depth interviews, observation, documents and focus group discussions (FGDs), to understand how the community interprets, accepts, or perceives State Defense attitudes socialized through the PKBN. The results of the study show that the efforts to socialize State Defense are very successful and adaptive, this is evidenced by the formation of State Defense forums in each region, socialization is carried out according to the tastes of young people, namely by making artists as models, and current youth habits such as drinking coffee, so the event